Perilaku Petani Terhadap Penggunaan Pupuk Organik Maggot di Desa Sukamakmur Kecamatan Ajung Kabupaten Jember - Adam Ramadhani; Nurul Dwi Novikarumsari (Universitas Sebelas Maret, 2025)
Organic fertilizer restores soil conditions as an effort to implement sustainable agriculture. This organic fertilizer is made from plants, animal manure, household waste, and decomposing organisms like maggots or black soldier fly. Tirto Bakti 2 group in Sukamakmur Village, Ajung Sub-district, Jember Regency, is the only farmer group utilizing maggots to make organic fertilizer, introduced by the Maggot Community Jember (KMJ). The use of maggot organic fertilizer by this group has reduced the need for chemical fertilizers from 7 to 5 quintals per hectare, saving costs by 40%. This quantitative study aims to understand farmers’ behavior towards using maggot organic fertilizer. The research was conducted in Sukamakmur Village with a population of 150 farmers, and a sample of 60 respondents was taken using the Slovin formula with a 10% margin of error and proportionate stratified random sampling method. Data were collected through observation, questionnaires, in-depth interviews, and documentation, then analyzed using the Likert scale and Rank Spearman analysis. The results showed that respondents using maggot fertilizer had high behavior, especially in the affective component, while non-users tended to have low behavior with a dominant behavioral component. Age, farming duration, and land ownership factors did not significantly relate to farmers’ behavior in using maggot organic fertilizer. However, education had a significant relationship, where higher education levels encouraged the use of this fertilizer.